Pentingnya Kepuasan Konsumen Untuk Meningkatkan Loyalitas Pelanggan - Ni Luh Nurkariani (ARTHA SATYA DHARMA, 2022)
The purpose of this study was to determine the effect of price, product quality, and service quality on increasing customer loyalty at UD. Surya Jati uses a quantitative approach where customer satisfaction is an intervening variable, then data collection uses documentation techniques and a survey sample of 85 people. In this survey, the sample is consumers who do business in a company, and the results of the impact analysis of this survey show that product quality has a positive and significant effect on customer satisfaction, and service quality is a positive and significant factor. Customer satisfaction and price have positive and negative effects on customer loyalty, product quality has positive and negative effects on customer loyalty, service quality has positive and negative effects, customer satisfaction has positive and negative effects on customer loyalty. Impact on discounts. Customer satisfaction has a positive and significant effect, service quality has a positive and significant effect on customer retention, and customer retention provides customer satisfaction.